(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Researchers elaborated on the idea of ‘reproductive citizenship,’ suggesting that individuals who make a reproductive contribution to modern western countries accumulate cultural capital in a homogenous manner. There has been some debate over whether or not reproduction is a characteristic of modern citizenship, but this article argues that it is, with reproductive hetero-sex being the standard against which other forms are measured. According to this theory, living outside of the norm creates a weakness known as ‘reproductive vulnerability,’ which is a state of vulnerability. By examining media portrayals of Australians who have travelled to India for surrogacy agreements, this study shows how Couples who journey for childbearing objectives have their fertility fragility stressed only to be ignored. The research closes by discussing the many, mutually incompatible dangers that are regarded and the portrayal of which stimulates, rather than hinders, thorough consideration of perinatal travel consideration of all people’s reproductive desires.